Intelectuales, estado y universidad. Algunas consideraciones sobre este vínculo complejo - Isola, Nicolás José (Diálogos Latinoamericanos, 2013)
This article aims to describe the different characterization which the intellectual figure has had throughout the twentieth century. Towards this end, special attention is given to the tradition of studies on intellectuals, exploring the diverse and recurring thematic focuses which this topic has covered, as well as the central role that intellectuals have played in modern history in Latin America and in Europe. In this framework, the conformation of the intellectual system, the different institutional forms that have been created around intellectuals and the leading role of universities are analyzed. The connection between intellectuals and temporality is examined: the tradition and the distance. Finally different intellectual profiles and their connection with politics are reviewed.